The Effect of Using Question-Answer Relationship (QAR) Strategy on Students’ Reading Comprehension in Descriptive Text of XII Grade at SMA Negeri 2 Perbaungan - Wahyuni Dwi Tiya, Zulfitri (Education Achievement: Journal of Science and Research, 2023)
The objective of this research was to obtain evidence of the effectiveness of the use of question-and-answer strategy relationships to students' reading ability in the description text This research uses quantitative research methods with experimental designs. The sample from this research was selected using a random sampling technique with a total sample of 70 students divided into two classes, an experimental class and a control class. The population of this research is class XII students of SMA Negeri 2 Perbaungan. The instrument used is a reading ability test. Before giving treatment, the students of both classes were given preliminary tests to find out what still exists in their ability to read explanatory texts. The test consists of 20 multiple-choice questions. At the end of the treatment, the students were given a post-test. Data from the two classes is processed using t-test. The average result from the post-test shows an improvement from the pre-test result to the post-test result. The results of the t-test show that the t-observed is greater than the t-table, namely t-observed 16.15 and t-table 2.00. The point is that the t-observed is greater than the t-table (16.15>2.00) with df 68 at a significant level of ? 0.025. After analyzing the data, it can be stated that Ho (Null Hypothesis) has been rejected and Ha (Alternative Hypothesis) has been accepted. Thus, the question-and-answer relationship strategy has an effect on students' reading comprehension in the description text.